Analysis on the application of joint tenancy in administration of real property in West Malaysia / Nur Akmal Adnan - Adnan, Nur Akmal (2023)
Joint ownership refers to the property owned by two or more persons. There are two major forms of joint ownership of real estate: joint tenancy and tenancy in common. Under common law, the joint tenancy has been applied as a mechanism to administer the estate, which takes effect after the joint owner's or joint tenant's death. If any of the joint tenants died, the left portion of the deceased will obligatorily be conceded to the surviving joint tenant and will not form part of the deceased's estate. In Penang, a joint tenancy contract is acknowledged by the National Land Code (Penang and Malacca Titles) Act 1963, that the survivor will succeed the whole estate under the rule of survivorship. The rights of survivorship were recognized by the statute as underlined in section 47(1)(c) of the Code and were embedded together between two or more individuals whose names were registered in the provisional record. Notwithstanding the above provisions, the National Land Code (Revised 2020) (Act 828) only recognizes tenancy in common and not joint tenancy. Consequently, the ownership will be shared not only during the lifetime of the joint tenant but extended even after death and will be considered as part of the deceased joint tenant's estate. This caused hardship to the surviving joint owner, especially when the joint owners had jointly acquired and developed the property. Hence, it is timely to explore the concept of joint tenancy under the common law and examine its validity under the law of succession in Malaysia. The research also aims to propose a regulatory framework and suitable mechanism for the land conveyance process in the application of joint tenancy. This research is based on qualitative research and analysis of the primary and secondary materials through the governing statutes, reported cases, semi-conducted interviews, focus group discussions and data obtained from the respective administrative bodies. For the comparative analysis, the research also explores the law and practice of joint tenancy in Singapore and Australia for the dual legal and Torrens systems, respectively. It is predicated that the joint tenancy application would give the proprietor more options in planning the management of his property and rightly give the advantage to the surviving joint tenant towards the full enjoyment of the property.